(untitled) (American Journal of Islam and Society, 2022)
Garrett Davidson’s new book, Carrying on the Tradition, is a significant contribution to the Western study of Sunni hadith. Through detailed analysis of a breath-taking range of hadith books and documentary sources, it identifies key features of hadith transmission that emerged during approximately the fourth/tenth century and were sustained in the Middle East and North Africa until the tenth/sixteenth century. During this period, which Davidson calls “post-canonical,” the purpose of chains of transmission (asānīd, isnād) was radically different from what it was during the first three centuries of Islam, when the canonical hadith books were compiled by scholars such as al-Bukhārī (d. 256/870) and al-Tirmidhī (d. 279/892). This transformation of the role of the chain of transmission had profound consequences on hadith transmission and, as Davidson demonstrates, has led many Western Islamicists to draw erroneous conclusions about hadith scholarship during this period.